(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Zakariyya Tamer, the renowned Syrian author, is widely regarded as a leading short fiction writer in the Arab world and the foremost author of Arabic children’s stories. His distinctive narrative style, blending minimalism, allegory, and symbolism, has earned widespread acclaim. His stories, marked by brevity and depth, challenge traditional storytelling structures, providing insights into the complex relationships between literature, culture, and society in the Arab world. This study examines Tamer’s life and contributions to modern Arabic literature, focusing on his innovative use of the short story to critically assess political and social structures. Through a critical analysis of his notable works, this research investigates Tamer’s narrative techniques, thematic concerns, and stylistic approach, illuminating his enduring legacy as a leading figure in contemporary Arabic literature. Ultimately, this study argues that Tamer’s contributions to the Arabic short story genre are essential for their stylistic and thematic innovation and enduring relevance, inspiring courageous and creative social and political commentary across generations of Arab writers.